Pengaruh Keadilan Organisasi Terhadap Perilaku Inovatif Dengan Kepercayaan Organisasi Sebagai Mediasi - Handayani, Ririn; Prasetya, Indra; Burhan, Burhan (LPPM Universitas Dharma Andalas, 2024)
The purpose of this research is to see the effect of organizational justice on innovative work behavior, as well as to prove the role of organizational trust in mediating the effect of organizational justice on innovative work behavior. The method used in this research is quantitative research which explains that the research paradigm emphasizes understanding of problems in social life based on the conditions of reality or natural settings that are holistic, complex and detailed. This research is descriptive and verificative in nature. The population of this research is members of Battalion Arhanud 13/PYB, totaling 525 people. Using the N population table developed by Krejcie and Morgan, the sample size is 217. The sample determination method used in this study is simple random sampling method. Data collection was carried out by means of field research, by submitting a structured questionnaire. Perceptions of organizational justice are measured by OJS (Moliner, 2004), organized by 12 items. Organizational trust is measured using Gabarro and Athos (1976) in Interpersonal Relations and Communications; which consists of 7 items as follows (Alshaabani, et al., 2022). Innovative behavior is measured by assessing how far each individual contributes to work based on Janssen (2000), totaling 9 items. The analysis technique used is the structural equation modeling (Structural Equation Modeling-SEM) based on variance or partial least squares (PLS). The results of the study found that organizational justice had a significant positive effect on innovative work behavior and organizational trust mediated the effect of organizational justice on innovative work behavior.